1983
DOI: 10.1016/s0022-5347(17)51007-1
|View full text |Cite
|
Sign up to set email alerts
|

Ketoconazole: A Novel and Rapid Treatment for Advanced Prostatic Cancer

Abstract: Ketoconazole is an orally administered broad-spectrum antifungal agent that acts through the inhibition of the steroid synthetic pathways. At high doses in humans ketoconazole can lower rapidly serum testosterone and maintain it in the castrate range with frequent administration. This property suggested that ketoconazole might be useful in the treatment of prostatic cancer. We report a case of prostatic cancer in which ketoconazole resulted in rapid and sustained reduction in serum androgens as well as rapid i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0
1

Year Published

1984
1984
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(48 citation statements)
references
References 5 publications
1
46
0
1
Order By: Relevance
“…In 1983, ketoconazole in high dose was identifi ed as able to produce castrate levels of androgens within 4-8 h of the fi rst dose (Trachtenberg and Point 1983), and represents an alternative treatment where urgent androgen ablation is required (Lowe and Bamberger 1990).…”
Section: Action Side Effectsmentioning
confidence: 99%
“…In 1983, ketoconazole in high dose was identifi ed as able to produce castrate levels of androgens within 4-8 h of the fi rst dose (Trachtenberg and Point 1983), and represents an alternative treatment where urgent androgen ablation is required (Lowe and Bamberger 1990).…”
Section: Action Side Effectsmentioning
confidence: 99%
“…9,10 Another serious problem with many chemotherapeutic agents is the side effects observed with aggressive high dose chemotherapy [11][12][13][14][15] that in severe cases extend to fatal myelo-suppression 16 and neuropathy. 17 Among several chemotherapeutic regimens being explored are docetaxel, in phase II trials, with response rates between 20-40%; 8,[18][19][20] estramustine plus taxane in phase III Southwest Oncology Group (SWOG) trial with objective responses in less than 20% of patients; 8,20,21 ketoconazole in Eastern Cooperative Oncology Group (ECOG)-sponsored phase III trial 8,[22][23][24] and carboplatin in phase II trials, showed significant prostate specific antigen (PSA) reductions, while less than 10% of patients exhibited a complete response. 25 Only a subpopulation of patients benefit from chemotherapy and since none of the agents are specific for CaP alongwith unacceptable toxicity profiles [30][31][32][33][34][35][36][37][38] makes it imperative to search for alternative chemotherapeutic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Ketoconazol has been shown to strongly decrease endogenous produc tion of gonadal and adrenocortical steroids and to in crease the biological half-life of coadministered drugs by inhibiting steroidogenic and drug-metabolizing cyto chrome P-450 enzymes [2][3][4][5][6]. Fluconazol, on the other hand, has been reported to interact neither with the endogenous endocrinological profile nor with the endo crine effects of coadministered oral contraceptives (OCs) [7], Since there are no such data available for SCH 39304, the present study was carried out.…”
Section: Introductionmentioning
confidence: 99%